The Spirit Lives On: Communication Seminars as a Surprisingly Hardy, Valuable, and Promising Heritage of NPAC - Kerry J. Brynes; Jim Evans (Journal of Applied Communications, 2016)
After many decades, dwindling numbers of communicators, extension personnel, and development professionals recall the National Project in Agricultural Communications (NPAC) of the 1950s and early 1960s. But around the world many professionals, scholars, and organizations can recognize the spirit and legacy of NPAC, which has had substantial impact well beyond its original national mission. NPAC became the springboard for a long-running series of communication seminars that built the capacity of foreign students, studying in the United States, to return home better able to communicate as change agents in fostering development. Seminars of NPAC also point to key ingredients for addressing urgent issues facing our nation and world today. This study addresses the origins, features, transitions, durability, and impacts of those communication seminars across nearly 60 years. The authors used historical analysis to reveal a surprising trail of service that leads to the present day and beyond. It provides new insights about how the NPAC communication training program has exerted more than 15 kinds of impact on agricultural development, on organizations at all levels throughout the world - and on individuals touched by it. The analysis highlights insightful, unpublished backstories about the communication training heritage of NPAC. It also identifies key elements of effective communication training programs and identifies opportunities for further research and practice. It could help readers identify professional development innovations the Journal of Applied Communications will advance and report during its second century.
Keywords: National Project in Agricultural Communications (NPAC); Professional Development; Communication Training; Extension Communication; Development Communication